Visualisation and Interaction for Remote Driving: Promoting Situation Awareness and Mitigating Cognitive Load for Remote Operators - Flising, Julia; Widerstrand, Ellen (My University, 2022)
As the world scrutinises its transportation network in the glaring light of climate change, remotely operated vehicles are emerging as an attractive solution to the problem. Boasting better safety, reliability and sustainability for the future, standardised freight trucks may be the pioneering project of its time. However, the operator of a remotely operated truck faces a unique set of challenges that needs addressing not only for their well-being but that of each stakeholder, from pedestrians to industry actors. In this Interaction Design Master Thesis the aim has been twofold: to investigate what key interface factors may be used to enhance the operator’s situation awareness when in demanding driving situations, and to examine what interface elements serve to mitigate cognitive load for the operator. This Research Through Design project has employed frameworks from Human- Centred Design (HCD) and IDEO’s 3i Model of Design Thinking to tackle the challenge through a user-focused process of two separate prototype usability tests. Each prototype was created from a foundation of formative research featuring methods ranging from literature reviews to expert interviews. The final product of this thesis work is a set of guidelines set to inform academia and industry actors alike of best-practice recommendations for the design of a remote operating interface. An iterative design process was carried out to ensure their good quality. These guidelines present ways in which to ensure the interface remains operator-supportive by tackling identified issues within automation, situation awareness and interaction design.
Keywords: Interaction design; remote operations; cognitive load; situation awareness; research through design; graphical user interface